BULAK SUMUR FRAMEWORK: IMPLEMENTATION SOCIAL CAPITAL VALUES TO OPTIMISE ZISWAF POTENTION - Putra, M Wahyu Pratama (State Institute of Islamic Studies (IAIN) Palu, 2021)
Zakat, Infaq, Alms and Waqf (ZISWAF) are potential instruments in improving the welfare of the community in the economic sector. However, this is not as expected, because there are many problems ranging from collection to distribution of funds, such as low public awareness, management and HR institutions that are less competent, to regulations that are less supportive. This problem is tried to be solved by researchers using the Bulak Sumur Framework through the application of social capital values ​​in the form of trust, norms and networks. This research uses a qualitative approach with the method of literature study. The research results obtained in optimizing the potential of ZISWAF are in terms of trust by conducting socialization, improving HR management, etc. Then in terms of norms by making regulations, policies and rules related to the ease of ZISWAF for the community, cooperation between institutions and related sanctions for Muslims who do not pay zakat. And finally from the network side which includes cooperation with technology institutions in making programs, collaboration between institutions in collecting and distributing starting from the realm of mosques and mass organizations as well as cooperation with influencers and YouTubers who have income and appeal to the community